EFEKTIVITAS KONSUMSI AIR KELAPA MUDA HIJAU TERHADAP NYERI DISMENOREA PADA SISWI DI SMKN 10 MUARO JAMBI - Simanjuntak, Ry Eny Mian Marisi Br.; Lestari, Ayu; Nurmisih, Nurmisih; Wuryandari, Ajeng Galuh (NHM PRESS, 2024)
Reproductive health issues that often occur among teenagers, especially adolescent girls, include menstrual disorders. Dysmenorrhea is a common menstrual disorder among teenagers. Dysmenorrhea causes discomfort in adolescents, necessitating management to alleviate it. This research is a quasi-experimental study with a two-group pretest-posttest design to determine the effectiveness of consuming young green coconut water on dysmenorrhea pain among female students at SMKN 10 Muaro Jambi in 2023. This study was conducted from January to July 2023. The study population consisted of all tenth and eleventh-grade female students in the 2022/2023 academic year, totaling 105 individuals. The sample size was 30 respondents, selected using the quota sampling technique. Data collection was conducted using the Numeric Rating Scale to assess dysmenorrhea pain levels in adolescents. Data were analyzed univariately and bivariately using the Wilcoxon and Mann Whitney tests. The results showed that young green coconut water (p-value 0.002) significantly affected dysmenorrhea pain in students, as the p-value was < 0.05. Young green coconut water effectively reduces dysmenorrhea pain in students. Therefore, schools are encouraged to promote the use of young green coconut water to address menstrual issues, including dysmenorrhea pain, making it a recommended method to alleviate and reduce dysmenorrhea pain.